Innovation through distance: The foundation of a satellite campus and its implication on teaching activities in a STEM subject - Thomas Baumgartner (Forum Neue Medien in der Lehre Austria, 2019)
This article discusses a technology-driven innovation in distance education at Universität Innsbruck that was commenced in 2016/17, when the already established undergraduate programme of Mechatronics was also introduced at a new satellite campus 200 kilometres away from the main campus. It looks at changing practices in teaching for this study progamme and articulates general managerial recommendations for introducing such large-scale changes. The analysis is supported by three interviews with leading faculty members and an ICT expert from Universität Innsbruck.